Prognostic significance of ımmunhistochemical axl expression in pancreas ductal adenocarcinomas - Ozden Oz; Asuman Argon; Tulu Ayata Kebat; Ozlem Ozdemir; Savas Yakan (Indian Journal of Pathology and Microbiology)
Introduction and Aim: Pancreas Ductal Adenocarcinomas (PDACs) are among the leading causes of cancer-related death. Tyrosine kinase receptors (TKRs) are responsible for cell plasticity, chemoresistance, immunosuppression and metastasis potential. Axl is a receptor of the TKR family, and it has come to the fore in cancer treatment in the last decade. This study aimed to investigate the relationship of immunohistochemical Axl expression with histological features and its prognostic importance in PDACs. Materials and Methods: Fifty-three patients who were operated on for PDAC between 2006-2017 were evaluated retrospectively. Features of tumors; size, lymphovascular invasion (LVI), perineural invasion (PNI), resection margin (RM), lymph node metastasis (LNM), differentiation, tumor-infiltrating lymphocyte, stage and overall survival were recorded. Immunohistochemically, membranous and or cytoplasmic staining was considered positive for Axl. Statistically, Pearson Chi-Square, Cox regression and Kaplan Mayer tests were used in the SPSS 21.0 program. Results: Axl was positive in 28 patients (52.8%). Axl positivity was found to be associated with the presence of LVI (P = 0.009) and LNM (P = 0.002) and was an independent prognostic factor in short survival (P = 0.006). Conclusion: It was found that increased expression of Axl, which is known to increase EMT-mediated metastasis in carcinogenesis, may be an indicator of local spread and poor prognosis in PDAC patients. In this respect, it can be promising as a targeted molecule in PDAC patient's individualized treatments.